A lightweight privacy-preserving truth discovery mechanism for IoT - Yingjie HE; Qiwei LI; Han SUN; Di GAO; Jianfeng DONG; Shuhua YANG (Dianxin kexue, 2021)
In order to solve diverse quality and privacy leakage of perceived data in fog-cloud integrated internet of things (IoT), a streaming encryption-based privacy-preserving truth discovery mechanism for IoT was proposed.Firstly, by utilizing shuffling and streaming encryption algorithms, the ground truths and the weights were anonymously updated on the cloud server and fog server, respectively, so that the collusion attacks between malicious attackers and cloud or fog servers could be resisted to defend against privacy leakage of IoT devices.Secondly, by adopting the Softmax function, the device weights were calculated on fog server, which reduces the error rate for calculating the ground truths.Finally, the theoretical analysis proved that the mechanism could protect privacy of the devices.And, the experimental results demonstrate that the proposed mechanism is an effective privacy-preserving trust discovery mechanism for large-scale IoT devices, which can outperform existing ones in computing efficiency.